Disruptive Technologies and Hospitality Entrepreneurs Perceptions: Strategic Approach of a Greek Destination - Varelas, Sotirios; Vrionis , Ivana Anucin (SPOUDAI Journal of Economics and Business, 2020)
The rapid development of Information and Communication Technologies (ICT) and the fast flow of data, allowed tourism enterprises to significantly increase the quality of their services. The intimacy of potential visitors with new technologies makes it convenient for the policy makers to use this technology to develop tourist destinations. The definition of Smart Tourism denotes the interconnection, synchronization and sharing of different travel-related technologies. This paper aims to endeavour, through research and study, the potential of a mature destination with a strong seasonality to exploit new technologies in order to renew it and transform it into a competitive, smart destination. The study will focus on the peninsula of Kassandra, one of the leading branded destinations in Greece, a typical example of the traditional "Sun and Sea" product. An analysis will, also, be made of the available destination data that will reveal whether Kassandra can be transformed into a destination with innovative actions, where technology will bring together all aspects of cooperation between authorities, infrastructures, tourists and residents and whether or not the tourism enterprises are informed and ready to participate. JEL Codes: Q55, Z32, M15